Nanospanlastics For Transdermal and Topical Drug Delivery: Formulation, Characterization, and Therapeutic Applications: Nanospanlastik untuk Penghantaran Obat Transdermal dan Topikal: Formulasi, Karakterisasi, dan Aplikasi Terapeutik - Fitria Rahmadiani; Esti Hendradi; Tutiek Purwanti (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2026)
Nanospanlastic is an elastic nanovesicular drug delivery system developed to enhance skin penetration, retention, and therapeutic efficacy in topical and transdermal applications. However, variations in formulation methods, characterization parameters, and evaluation approaches across studies have limited the standardization of its performance. This review was conducted systematically in accordance with the PRISMA guidelines. A comprehensive literature search was performed using international electronic databases, including ScienceDirect, Springer, PubMed, SAGE, and Taylor & Francis online, covering publications from 2015 to 2025. The keywords used were "nanospanlastic,” “spanlastic,” “nanovesicles,” “transdermal,” “topical,” “characterization,” and “application.” Articles were screened based on predefined inclusion and exclusion criteria, and 32 eligible studies were selected for qualitative meta-synthesis analysis. This article presents a cross-study comparative analysis focusing on formulation factors, physicochemical characteristics, deformability, stability, and dermatological applications. The synthesis results indicate that surfactant–edge activator composition, manufacturing methods, and component ratios significantly influence particle size, polydispersity index (PDI), entrapment efficiency, and deformability index, which, in turn, determine skin penetration and retention performance. Although nanospanlastic demonstrates improved permeation and promising pharmacological effects, challenges remain regarding long-term stability, chronic safety, and scalability for GMP-based industrial production. This review highlights critical research gaps and proposes future development directions, including formulation optimization, harmonization of characterization methods, and broader clinical validation. Therefore, nanospanlastic represents a promising innovative platform for dermatological drug delivery but requires further systematic and translational development